KORELASI ANTARA STRES PSIKOLOGIS DENGAN NILAI AMBANG DENGAR DI LINGKUNGAN BISING MESIN PADA PEKERJA PABRIK KONVEKSI - , Tan'im; , DR. dr. Bambang Udji Djoko Rianto, Sp.THT-KL(K), M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Noise in long and continous duration can cause hearing loss and noise is a pschycological stressor and physical factors that can affect hearing function. Noise above 85 dB not only causing a complaint in ear and hearing organ, but also causing an increase of blood pressure, sleep disorder, indigestion, increase of emotion and another disorder that is cause by pschycological stress. This study was using a cross sectional analytic design to know the correlation between pschycological stress with hearing threshold on convection factory workers. Study location was in PT MTG Yogyakarta, with the subject amount were 63 people whom fulfilled the inclusion and exclusion criteria. Audiometry test were done on study subjects, and interview and Hamilton rating scale questioner were used to know the pschycological stress. Data analysis were using Spearmanâs correlation test, then it was been drawed on scatter plot graphic (disperse diagram). Result: correlation test between pschycological stress with hearing threshold in frequency 125 â 8000 Hz on both right and left ear was found that there was no significant correlation (p > 0,05), based on air conduction measurement, weak correlation strength (right ear rxy = 0,034 â 0,185, left ear rxy = 0,071 â 0,190), while based on bone conduction measurement in frequency 250-4000Hz was found that there was no significant (p > 0,05), weak correlation strenght (right ear rxy = 0,015 â 0,175, left ear rxy = 0,017 â 0,168). Summary: there is a very weak correlation between pschycological stress with hearing threshold on both right and left ear in convection factory workers.